HIDROGEOLOGI DAN PEMODELAN PLUME DI TPA PASIR IMPUN DENGAN METODA MISE-A-LA-MASSE BERDASARKAN ANALOGI MODEL ALIRAN LISTRIK DAN ALIRAN AIRTANAH - Wahyu Widodo, Untung
Abstracts: MISE-A-LA-MASSE electrical flow through conductive porous media can be simulated by two-dimensional finite difference saturated groundwater model such as MODFLOW. A new technique for using an existing numerical code for simulating MISE-A-LA-MASSE electrical flow is described in this study. This technique is based on analogical model between electrical flow and groundwater flow. By adjusting the input data and incorporating a change in variables from electrical flow to groundwater flow within the MODFLOW, spherical electrical flow through contaminated porous media can be approximated in two-dimensions. This study also presents a technique to identify contaminated groundwater from point source (landfill) indirectly using MISE-A-LAMASSE method. To achieve the optimal result, this study was also supported by local hydrogeological mapping around the Pasir Impun landfill. The analysis using MISE-A-LA-MASSE method, local hydrogeological mapping, and MODFLOW simulation produce relatively similar results and can be used to explain the conditions of contaminated groundwater (plume) originated from Pasir Impun landfill.